Cursory Viewpoint on Transnistria as the Focus of the Russian Federation Policy - Telenko, Olha; Prysiazhniuk, Yuriy (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The article outlines cursory viewpoint on Transnistria as the focus of the Russian Federation policy. Russia pursues political interests in Transnistria connected with its geostrategic ambitions on the post-Soviet state. It is revealed that Moscow has a great impact on the life of Transnistria and cooperates with Tiraspol in political, military, social, cultural, and economic spheres. It is discussed that Russian military presence in this de facto state helps not only to control Transnistria but also Moldova concerning its geopolitical choice. In the article Russia’s activity concerning conflict resolution in Transnistria is shown. A special attention is paid to the Kozak Plan aiming at unification of Transnistria and Moldova, according to which too-extensive rights to Transnistria had to be given. Although this plan was not implemented, in fact now its idea is promoted gradually through convergence of Moldova and Transnistria. In the article it is stressed that russification of the region influences on the mood of the population concerning the future status of the region. Social and economic relations between Russia and Transnistria are researched. It is revealed that all three presidents of this de facto state had close ties with the Russian government and coordinated their politics with it. It is discussed that officially Russia supports territorial integrity of Moldova but at the same time it gives comprehensive support of Transnistria. Although it is not declared in the documents, now the Russian Federation favours status quo in Transnistria.

Artykuł przedstawia rosyjski punk punkt widzenia na Naddniestrze, które jest w centrum uwagi polityki Federacji Rosyjskiej. Rosja realizuje polityczne interesy w Naddniestrzu związane z jej geostrategicznymi ambicjami na przestrzeni poradzieckiej. Okazuje się, że Moskwa ma ogromny wpływ na życie regionu i współpracuje z Tyraspolem na płaszczyźnie politycznej, militarnej, społecznej, kulturowej i gospodarczej. Mówi się, że rosyjska obecność wojskowa w tym de facto państwie pomaga nie tylko kontrolować Naddniestrze, ale także Mołdawię, jeżeli chodzi o jej wybór geopolityczny. W tym artykule pokazano aktywność Rosji w zakresie rozwiązywania konfliktów w Naddniestrzu. Szczególną uwagę zwraca się na plan Kozaka, mający na celu zjednoczenie Naddniestrza i Mołdawii, zgodnie z którym należało nadać Naddniestrzu zbyt rozległe prawa. Chociaż plan ten nie został zrealizowany, w rzeczywistości jego idea jest obecnie stopniowo promowana poprzez zbliżenie Mołdawii i Naddniestrza. W artykule podkreślono, że rusyfikacja regionu wpływa na nastroje ludności dotyczące przyszłego jego statusu. Zbadane są relacje społeczno-gospodarcze między Rosją a Naddniestrzem. Okazuje się, że wszyscy trzej prezydenci tego de facto państwa mieli bliskie powiązania z władzami rosyjskimi i koordynowali z nimi swoją politykę. Mówi się, że Rosja oficjalnie popiera integralność terytorialną Mołdawii, ale jednocześnie udziela kompleksowego wsparcia regionowi. Choć nie jest to deklarowane w dokumentach, obecnie Federacja Rosyjska faworyzuje status quo w regionie.
Ogólny punkt widzenia na Naddniestrze jako priorytet polityki Federacji Rosyjskiej
Keywords: Transnistria; Russia; de facto state; cooperation; international recognition; Naddniestrze; Rosja; państwo de facto; współpraca; uznanie międzynarodowe